2021
DOI: 10.1063/5.0058920
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric quantum mechanics and coherent states for a deformed oscillator with position-dependent effective mass

Abstract: We study the classical and quantum oscillator in the context of a non-additive (deformed) displacement operator associated with a position-dependent effective mass by means of the supersymmetric formalism. From the supersymmetric partner Hamiltonians and the shape invariance technique, we obtain the eigenstates and the eigenvalues along with the ladders operators, thus showing a preservation of the supersymmetric structure in terms of the deformed counterpartners. The deformed space in supersymmetry allows to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…61. This work is a continuation of Ref. 61. However, we address here the problem of the deformed oscillator subject to an asymmetric potential (which also includes the effect of PDM), as well as properties of its coherent states.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…61. This work is a continuation of Ref. 61. However, we address here the problem of the deformed oscillator subject to an asymmetric potential (which also includes the effect of PDM), as well as properties of its coherent states.…”
Section: Introductionmentioning
confidence: 95%
“…Some theoretical studies have been developed with the aim of introducing the effect of a PDM by means of deformed algebraic structures. [56][57][58][59][60][61][62][63] More specifically, the effect of a PDM can be described by a Schrödinger equation where the usual derivative is replaced by a deformed derivative operator, and the Hamiltonian operator is expressed in terms of a deformed linear momentum operator. 56,60,62 For instance, Costa Filho et al 56 introduced a displacement operator that leads to non-additive spatial translations Tγ (ε)|x = |x + (1 + γx)ε , in which γ is a deformation parameter with inverse length dimension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find cases of our Dunkl-Schrödinger equation that admits closed-form solutions, we adapt point transformations and Darboux transformations to the present scenario. Both of these techniques have been widely applied to nonrelativistic quantum systems with position-dependent mass, for example in the study of finite gap systems [4], the problem of operator ordering in Hamiltonians [16], and the construction of coherent states [8]. In contrast to these and related applications, to the best of our knowledge point transformations and Darboux transformations have not been applied yet to Dunkl-Schrödinger equations equipped with both a position-dependent mass and an energy-dependent potential.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of the uncertainty relation in x and p, we have shown that the ground state is a squeezed coherent state (CS). Being the minimum uncertainty state, a CS mostly resembles the classical states [64][65][66][67]. On the other hand, the Wigner quasiprobability distributions (WQD) provide a phase-space representation of QM.…”
Section: Introductionmentioning
confidence: 99%